CSR and Sustainability in the Cement Industry of Rajasthan: A Comparative Study of Company Performance and Stakeholders' Engagement (Based on Secondary Survey Reports) (International Journal of Scientific Research in Science and Technology, 2025)
This study aims to analyze the Corporate Social Responsibility (CSR) and sustainability practices in the cement industry of Rajasthan through a comparative approach. By focusing on secondary survey reports, the research examines the performance of cement companies in terms of their CSR initiatives, sustainability efforts, and stakeholder engagement. The cement industry, being a significant contributor to environmental impact, plays a crucial role in implementing eco-friendly practices, reducing carbon footprints, and ensuring social welfare in the surrounding communities. This study evaluates how various companies in Rajasthan have integrated sustainable development goals (SDGs) into their operations, with an emphasis on energy efficiency, waste management, water conservation, and renewable energy adoption. Additionally, it explores the involvement of stakeholders, including employees, local communities, and regulatory bodies, in promoting sustainable practices. Through this comparative study, the research highlights the strengths and weaknesses of the industry’s CSR initiatives and offers insights into enhancing corporate governance and stakeholder collaboration for sustainable development in the cement sector. The findings provide valuable recommendations for cement companies, policymakers, and stakeholders to improve their CSR and sustainability frameworks, ensuring a more sustainable and socially responsible future for the cement industry in Rajasthan.
Keywords: Corporate Social Responsibility (CSR); Sustainability Practices; Cement Industry; Rajasthan; Stakeholder Engagement; Environmental Sustainability